Sobrevivência e movimento pós-soltura de jacutingas (Aburria jacutinga) (Spix, 1825) reintroduzidas na Serra da Mantiqueira - Bezerra, Aline Sales (2023)
The black-fronted piping guans (Aburria jacutinga) are large arboreal, frugivorous birds, with an important role as seed dispersers, with emphasis on the fruits of Euterpe edulis, which is an important item in their diet. It is a neotropical species, with a natural distribution occurring only in the Atlantic Forest of Brazil from southern Bahia to Rio Grande do Sul, northern Argentina and Paraguay. However, habitat loss and especially predatory hunting represent a constant threat to the populations of black-fronted piping guans with reports of killings since the 19th century. With populations significantly reduced, isolated and with local extinctions in its distribution area, the black-fronted piping guans are classified as an Endangered species in global and national lists of threatened species. The loss of this large frugivore is a conservation concern due to the damage to seed dispersal, which is a key step in the regeneration of forest ecosystems. Faced with such a scenario, the reintroduction of individuals born under human care is a viable alternative for the preservation of these birds. The reintroduction process aims to re-establish a viable population that survives without human intervention, and requires attention in the planning phase from the selection and preparation of candidates, suitability of the habitat for release, the type of release and adequate monitoring that will identify the causes of success and mortality. There are different understandings about the definitions of successful reintroduction, but there is consensus on three objectives: the reintroduction must ensure the survival of the founding population, the establishment in the release area with the reproduction of this generation and its descendants and, finally, the permanence of the restored population. Dispersion is a factor that permeates these three phases, especially the establishment phase, which is marked by the survival and reproduction of the founding population and is sensitive to dispersion due to the size and composition of this initial population. For this reason, it is necessary to know the factors that affect the processes of survival and dispersion of released individuals, which in this study will be addressed through the evaluation of survival rates and their related elements, description of dispersion with the individual variation of movement behavior and the use of the territory and its landscape attributes. Post-release monitoring of black-fronted piping guans reintroduced by the NGO SAVE Brasil in the Serra da Mantiqueira, in the state of São Paulo, using radio-telemetry searches, allowed tracking of 34 individuals over five years. This process brought contributions that can support future reintroductions regarding the post-release survival estimate with the identification of the critical period of mortality, which can be used to assess the number of black-fronted piping guans for the next releases, indications about the individual patterns of the movement and dispersion that reflect an adaptation to free life, although they still do not indicate the stabilization of released individuals, and the understanding about the use of the territory that can guide landscape conservation strategies considering the mobility of these animals.